2019
DOI: 10.1097/jxx.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Use of PHQ-9 and pharmacogenetic testing in clinical practice

Abstract: Background: This project evaluated the clinical use of pharmacogenetic testing in an outpatient psychiatric practice, integrated a standardized measure for assessing depressive symptoms, and captured data regarding treatment efficacy. Local Problem: According to the Centers for Disease Control and Prevention (2016), more than 10% of all outpatient office visits include a depression-related diagnosis. Patients who require more medication trials to experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…These comprised 1 SR, 9 1 HTA, 10 4 RCTs, [11][12][13][14][15] 1 NRS, 16 1 cohort study with historical control, 17 and 2 uncontrolled before-and-after studies. 18,19 Of the RCTs, 2 publications by Ruaño et al reported results from the same trial: 13,14 1 study described the main results 13 and the other summarized findings based on subgroup analyses. 14 The publication by Huilei et al 16 described an intervention study; however, since randomization was not mentioned, it is assumed that the study was non-randomized for the purpose of this report.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 4 more Smart Citations
“…These comprised 1 SR, 9 1 HTA, 10 4 RCTs, [11][12][13][14][15] 1 NRS, 16 1 cohort study with historical control, 17 and 2 uncontrolled before-and-after studies. 18,19 Of the RCTs, 2 publications by Ruaño et al reported results from the same trial: 13,14 1 study described the main results 13 and the other summarized findings based on subgroup analyses. 14 The publication by Huilei et al 16 described an intervention study; however, since randomization was not mentioned, it is assumed that the study was non-randomized for the purpose of this report.…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…The authors of the included SR were from Qatar 9 and those who authored the HTA 10 were from Canada. Of the remaining 8 studies (where 1 was reported in 2 publications), 4 were conducted in the US, 11,13,14,18,19 1 in Canada, 12 1 in Russia, 15 1 in China, 16 and 1 in Germany 17 (the primary author's affiliations were both Switzerland and Germany).…”
Section: Country Of Originmentioning
confidence: 99%
See 3 more Smart Citations